Rhythmic Gymnastics Training for Cheerful Youth Towards a Fit Indonesia 2045 - Bambang Priyono; Ranu Baskora Aji Putra; Roas Irsyada; Rachmad Irfan Nur; Asyifa Tsalisafriana (CV. Rayyan Dwi Bharata, 2025)
The characteristics of adolescent students (aged 10–19 years) at the Senior High School (SMA) level demand an effective learning design that supports body health and physical fitness. Creative rhythmic gymnastics accompanied by music is a relevant physical activity proven to reduce stress, improve school performance, and develop students' physical, cognitive, and social qualities. This community service focused on